Hybrid ZTE/Dixon MR‐based attenuation correction for quantitative uptake estimation of pelvic lesions in PET/MRI - Leynes, Andrew P. (John Wiley and Sons Inc., 2017)

(untitled) (Med Phys)
PURPOSE: This study introduces a new hybrid ZTE/Dixon MR‐based attenuation correction (MRAC) method including bone density estimation for PET/MRI and quantifies the effects of bone attenuation on metastatic lesion uptake in the pelvis. METHODS: Six patients with pelvic lesions were scanned using fluorodeoxyglucose (18F‐FDG) in an integrated time‐of‐flight (TOF) PET/MRI system. For PET attenuation correction, MR imaging consisted of two‐point Dixon and zero echo‐time (ZTE) pulse sequences. A continuous‐value fat and water pseudoCT was generated from a two‐point Dixon MRI. Bone was segmented from the ZTE images and converted to Hounsfield units (HU) using a continuous two‐segment piecewise linear model based on ZTE MRI intensity. The HU values were converted to linear attenuation coefficients (LAC) using a bilinear model. The bone voxels of the Dixon‐based pseudoCT were replaced by the ZTE‐derived bone to produce the hybrid ZTE/Dixon pseudoCT. The three different AC maps (Dixon, hybrid ZTE/Dixon, CTAC) were used to reconstruct PET images using a TOF‐ordered subset expectation maximization algorithm with a point‐spread function model. Metastatic lesions were separated into two classes, bone lesions and soft tissue lesions, and analyzed. The MRAC methods were compared using a root‐mean‐squared error (RMSE), where the registered CTAC was taken as ground truth. RESULTS: The RMSE of the maximum standardized uptake values (SUV ( max )) is 11.02% and 7.79% for bone (N = 6) and soft tissue lesions (N = 8), respectively, using Dixon MRAC. The RMSE of SUVmax for these lesions is significantly reduced to 3.28% and 3.94% when using the new hybrid ZTE/Dixon MRAC. Additionally, the RMSE for PET SUVs across the entire pelvis and all patients are 8.76% and 4.18%, for the Dixon and hybrid ZTE/Dixon MRAC methods, respectively. CONCLUSION: A hybrid ZTE/Dixon MRAC method was developed and applied to pelvic regions in an integrated TOF PET/MRI, demonstrating improved MRAC. This new method included bone density estimation, through which PET quantification is improved.